Rare earth metal oxide‐doped reduced graphene‐oxide nanocomposite as binder‐free hybrid electrode material for supercapacitor application. (28th January 2021) - Muthuselvi, M.; Jeyasubramanian, K.; Hikku, G.S.; Muthuselvan, M.; Eswaran, Muthusankar; Senthil Kumar, N.; Ponnusamy, Vinoth Kumar
Summary: In this study, rare earth metal‐oxide (yttrium oxide nanoparticles, Y2 O3 NPs) doped reduced graphene oxide nanosheets (rGONSs) nanocomposites (Y‐rGO) were prepared and applied as hybrid electrode materials to evaluate the supercapacitor performances. For comparative analysis, various ratios of Y2 O3 NPs doped rGONSs nanocomposites were prepared by dispersing different amounts (3, 5, and 10 wt%) of Y2 O3 NPs in the aqueous rGONSs dispersion under facile ultrasonication process. As prepared Y‐rGO nanocomposites were characterized towards its physicochemical and electrochemical properties using powder X‐ray diffraction, Fourier‐transform infrared spectroscopy, field‐emission scanning electron microscopy, X‐ray photoelectron spectroscopy, and electrochemical analysis such as cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS) and galvanostatic charge‐discharge (GCD) analysis. Electrochemical studies reveal that 5 wt% Y‐rGO displays improved supercapacitor performance with a high specific capacitance of 190 Fg −1 at 10 mVs −1 and also exhibits excellent cyclic retention of 88% due to the intercalation of rGO and less contact resistance facilitated by Y2 O3 NPs when compared with 3 wt% Y‐rGO and 10 wt% Y‐rGO nanocomposites. Further, 5 wt% Y‐rGO display a very low charge‐transfer resistance of 0.001 Ω, suggesting its commercial viability for energy storage devices. Abstract : Rare earth metal‐oxide Y2O3NPs‐doped rGONSs nanocomposites (Y‐rGO) were utilized as hybrid electrode materials to evaluate the supercapacitor performances. Physicochemical characterizations ensure structural geometry, morphological views, and elemental compositions. Different mass ratios of Y2O3NPs (3, 5, and 10 wt%) doped rGONSs nanocomposites were prepared and investigated towards its supercapacitive performances. The hybrid‐electrode material displayed a higher specific capacitance of 190 Fg‐1 on introducing 5 wt% Y‐rGO into 95% rGO matrix. The prepared nanocomposite material showed high cyclic retention of about 88% over 10 000 charge‐discharge cycles.